CSS3 for dummies - Mueller, John Paul 1958- (John Wiley & Sons, Inc., 2014)
CSS3 is loaded with features like better mobility, cleaner code, and less maintenance. Learn to use CSS3 shortcuts; work with fonts, colors, and graphics; customize the interface with jQuery UI; and more.